Combined novel homozygous variants in both SGPL1 and STAT1 presenting with severe combined immune deficiency: case report and literature review - Roa-Bautista, Adriel; Sohail, Mahreen; Wakeling, Emma; Gilmour, Kimberly C.; Davis, Mark; Gait, Anthony; Lucchini, Giovanna; Cox, David; Elfeky, Reem; Kusters, Maaike (Frontiers in Immunology, 2023)
Background: Sphingosine phosphate lyase insufficiency syndrome (SPLIS) is associated with biallelic variants in SGPL1, comprising a multisystemic disease characterized by steroid-resistant nephrotic syndrome, primary adrenal insufficiency, neurological problems, skin abnormalities and immunodeficiency in described cases. Signal transducer and activator of transcription 1 (STAT1) plays an important role in orchestrating an appropriate immune response through JAK-STAT pathway. Biallelic STAT1 loss of function (LOF) variants lead to STAT1 deficiency with a severe phenotype of immunodeficiency with increased frequency of infections and poor outcome if untreated. Case presentation: We report novel homozygous SGPL1 and STAT1 variants in a newborn of Gambian ethnicity with clinical features of SPLIS and severe combined immunodeficiency. The patient presented early in life with nephrotic syndrome, severe respiratory infection requiring ventilation, ichthyosis, and hearing loss, with T-cell lymphopenia. The combination of these two conditions led to severe combined immunodeficiency with inability to clear respiratory tract infections of viral, fungal, and bacterial nature, as well as severe nephrotic syndrome. The child sadly died at 6 weeks of age despite targeted treatments. Conclusion: We report the finding of two novel, homozygous variants in SGPL1 and STAT1 in a patient with a severe clinical phenotype and fatal outcome early in life. This case highlights the importance of completing the primary immunodeficiency genetic panel in full to avoid missing a second diagnosis in other patients presenting with similar severe clinical phenotype early in life. For SPLIS no curative treatment is available and more research is needed to investigate different treatment modalities. Hematopoietic stem cell transplantation (HSCT) shows promising results in patients with autosomal recessive STAT1 deficiency. For this patient’s family, identification of the dual diagnosis has important implications for future family planning. In addition, future siblings with the familial STAT1 variant can be offered curative treatment with HSCT.